2009
DOI: 10.1177/0898010108327212
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Serenity Scale

Abstract: Spirituality is recognized as being an essential component of holistic nursing practice. As nurses expand their use of spiritual interventions, it is important to document outcomes related to nursing care. The Serenity Scale appears to capture a dimension of spirituality, a state of acceptance, inner haven and trust that is distinct from other spirituality instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 19 publications
3
22
1
Order By: Relevance
“…We analyzed the SF-12 using a scoring algorithm coded from the user's manual that is based on the 1998 norms for the U.S. population (Ware, Kosinski, Turner-Bowker, & Gandek, 2002). The Brief Serenity Scale is a relatively new measure of spirituality and well-being that was developed in response to a need for a shorter measure of serenity than previously established measures (Kreitzer et al, 2009), and which has been used in prior studies of the nursing population (Penque, 2009) and MBSR (Gross et al, 2009). The Jefferson Scale of Physician Empathy is designed to measure empathy among physicians, health professionals, and medical students (Hojat et al, 2001), and its use has been validated among nurses (Fields et al, 2004), and nursing students (Ward et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the SF-12 using a scoring algorithm coded from the user's manual that is based on the 1998 norms for the U.S. population (Ware, Kosinski, Turner-Bowker, & Gandek, 2002). The Brief Serenity Scale is a relatively new measure of spirituality and well-being that was developed in response to a need for a shorter measure of serenity than previously established measures (Kreitzer et al, 2009), and which has been used in prior studies of the nursing population (Penque, 2009) and MBSR (Gross et al, 2009). The Jefferson Scale of Physician Empathy is designed to measure empathy among physicians, health professionals, and medical students (Hojat et al, 2001), and its use has been validated among nurses (Fields et al, 2004), and nursing students (Ward et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The focus of the research was IO services and in Australia, pastoral care services are not classified as an IO service [ 3 , 30 , 31 ]. The researchers recognise that the boundaries can be blurred, as T&CM wellbeing services such as meditation and mindfulness may draw on religious philosophies and traditions, and spirituality (rather than religiousness) is considered to be a domain of ‘holistic health’ [ 32 , 33 ]. Nevertheless, the decision was made that prayer and pastoral care were outside the scope of this research project.…”
Section: Methodsmentioning
confidence: 99%
“…The authors determined that the Brief Serenity Scale should have small-to-moderate positive correlations (r = .3 to .5, representing 10%-25% shared variation) with concepts of mindful awareness and positive affect. Factors that were highly correlated with serenity included "Trust" issues: trusting that life events happen to fit a plan, which is larger and more gentle than the participant can know, that the subject can see good things in the painful things that happened to him or her, that the subject did not have to understand why something happened to accept it, and that the subject trusts that everything happens as it should (Kreitzer et al, 2009). …”
Section: Severely Burnedmentioning
confidence: 97%
“…Coward also found that this phenomenon could be experienced by more than one person at a time, meaning that the nurse-patient experience could evolve into one of a shared transcendence, leading to a sense of shared serenity (Coward, 1990). Kreitzer et al (2009) conducted a psychometric analysis of the instrument, the Serenity Scale, which is used to measure dimensions of spirituality and well-being that contribute to serenity and are sensitive to nursing interventions. Like spirituality, serenity is a multidimensional construct that may be defined in a variety of ways.…”
Section: Defining Serenitymentioning
confidence: 99%